Electrically tunable all-PCM visible plasmonics - Sreekanth, Kandammathe Valiyaveedu (2021)
The realization of electrically tunable plasmonic resonances in the ultraviolet (UV) to visible spectral band is particularly important for active nanophotonic device applications. However, the plasmonic resonances in the UV to visible wavelength range cannot be tuned due to the lack of tunable plasmonic materials. Here, we experimentally demonstrate tunable plasmonic resonances at visible wavelengths using a chalcogenide semiconductor alloy such as antimony telluride (Sb2Te3), by switching the structural phase of Sb2Te3 from amorphous to crystalline. We demonstrate the excitation of a propagating surface plasmon with a high plasmonic figure of merit in both amorphous and crystalline phases of Sb2Te3 thin films. We show polarization-dependent and -independent plasmonic resonances by fabricating one and two-dimensional periodic nanostructures in Sb2Te3 thin films, respectively. Moreover, we demonstrate electrically tunable plasmonic resonances using a microheater integrated with the Sb2Te3/Si device. The developed electrically tunable Sb2Te3-based plasmonic devices could find applications in the development of active color filters.